Relevansi Keputusan Dirjen Bimas Islam Nomor DJ.II/542 Tahun 2013 tentang Kursus Pranikah terhadap Keharmonisan Rumah Tangga di Kemenag Bandar Lampung - Novalia, Sisca; Khairuddin, Khairuddin; Zuhraini, Zuhraini (Fakultas Syariah INSURI Ponorogo, 2021)
This study was made to analyze the implementation of the Decision of the Director General of Islamic Community Guidance Number DJ.II / 542 of 2013 concerning the Prenuptial Course at the Office of the Ministry of Religion in the City of Bandar Lampung and to determine the relevance of taking the Prenuptial Course to household harmony. This type of research uses Field Research, where researchers go directly to the field to obtain strong, objective and actual data. Researchers will go to the field to obtain authentic, accurate, detailed and in-depth data. The results of this study indicate that the implementation of the Decree of the Director General of Guidance for the Islamic Community Number DJ.II / 542 of 2013 concerning prenuptial courses is quite effective. couples to reduce disputes in the family, divorce and conflict, so that they become provisions for realizing a peaceful, prosperous, safe, peaceful family and truly creating a sakinah mawadah warahmah family. After fulfilling the existing procedures, the bride and groom get a foundation book for the sakinah family and a certificate. However, if viewed from the level of effectiveness there are still several weaknesses, including the lack of availability of funding to cover all training needs, the seriousness of the participants is not optimal, the lack of attendance and the level of activity of participants in taking pre-marital training courses, and the continuity of pre-marital course activities that have not been optimally scheduled.